In search of excellence in project management : successful practices in high performance organizations - Kerzner, Harold (New York : Van Nostrand Reinhold, 1998)
The search for excellence; Foundations of project management; Driving forces; Project management systems and tools; Planning for excellence; Basics of modern project management; Integrated management processes; Culture; Management support; Training and education; Informal project management; Behavioral excellence; Rising stars and future directions.
Includes index.
Keywords: Industrial management; Project management; Industrial management